Hydroxychloroquine in patients with systemic lupus erythematosus: how much is enough? - Guillermo Ruiz-Irastorza; Daniel Martín-Iglesias; Ioana Ruiz-Arruza; Fernando Arizpe; Victor Moreno-Torres; Diana Paredes-Ruiz; Valerio Campos-Rodriguez; Laura Amo (Lupus Science and Medicine)
Objective To assess the daily and weight-adjusted dosages of hydroxychloroquine (HCQ) and the effects on long-term remission in the Lupus-Cruces cohort.Methods Observational study of routine clinical care data. We selected inception patients treated with HCQ with at least 5 years of follow-up. Prolonged remission was achieved when patients fulfilled deﬁnitions of remission in systemic lupus erythematosus remission criteria in five consecutive yearly visits. The associations between the weight-adjusted dose of HCQ during 5 years and prolonged remission were analysed. We also investigated the associations between prednisone doses, immunosuppressives (IS) and other antimalarial use with HCQ doses.Results 150 inception patients fulfilled the inclusion criteria. The mean starting dose of HCQ was 206 mg/day. The mean weight-adjusted starting dose of HCQ was 3.1 mg/kg/day with no patients treated with doses ≥5 mg/kg/day. Treatment with HCQ was maintained during the whole 5-year follow-up time in 148 patients (98%). The mean dose of HCQ during the 5-year follow-up was 194.6 mg/day (2.9 mg/kg/day). 108 patients (72%) were in prolonged remission. The mean weight-adjusted dose of HCQ per patient did not differ between those who did and did not achieve prolonged remission (2.9 vs 3 mg/kg/day, p=0.5). The dose of prednisone per patient (mean 2.3 mg/day during the 5-year follow-up) did not differ according to the weight-adjusted dose of HCQ. The mean weight-adjusted HCQ dose during the whole follow-up was the same in patients treated or not with IS or with mepacrine.Conclusions With the use of HCQ at stable doses of 200 mg/day (or 3.0–3.5 mg/kg/day) as the background therapy in patients with systemic lupus erythematosus, the majority of patients achieved prolonged remission.